2021
DOI: 10.1007/s00265-021-03034-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year assessment of variability in spatial and social relationships in a subterranean rodent, the highland tuco-tuco (Ctenomys opimus)

Abstract: In some species, populations routinely contain a mixture of lone and group-living individuals. Such facultative sociality may reflect individual differences in behavior as well as adaptive responses to variation in local environmental conditions. To explore interactions between individual- and population-level variabilities in behavior in a species provisionally described as facultatively social, we examined spatial and social relationships within a population of highland tuco-tucos (Ctenomys opimus) at Laguna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Moreover, comparisons of results based on 95% versus 50% AKDEs indicated that overlap was largely restricted to the periphery of individual home ranges. Collectively, these findings suggest that although overlap of home ranges is common, patterns of space use by adults in the study population are not consistent with those for group-living species of burrow-dwelling rodents (Lacey 2000;O'Brien et al 2021). Instead, these results appear to reflect a colonial organization, in which generally solitary individuals live in close proximity to one another, leading to overlap of the areas occupied by different animals (Burda et al 2000).…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, comparisons of results based on 95% versus 50% AKDEs indicated that overlap was largely restricted to the periphery of individual home ranges. Collectively, these findings suggest that although overlap of home ranges is common, patterns of space use by adults in the study population are not consistent with those for group-living species of burrow-dwelling rodents (Lacey 2000;O'Brien et al 2021). Instead, these results appear to reflect a colonial organization, in which generally solitary individuals live in close proximity to one another, leading to overlap of the areas occupied by different animals (Burda et al 2000).…”
Section: Discussionmentioning
confidence: 66%